Efeito antinociceptivo e anti-inflamatório do óleo da polpa de pequi Caryocar coriaceum Wittm na artrite induzida por zymosan em ratos - Oliveira, Francisco Fábio Bezerra de (2013)
Arthritis is an inflammatory disease that affects synovial joints. The most common symptoms are increased sensitivity to joint pain (hyperalgesia or hypernociception) and edema. An alternative to treating the disease is the inclusion of medicinal plants. The oil extracted from the fruits of Pequi (Caryocar coriaceum Wittm) has wide applicability in popular medicine. Pre-clinical tests have demonstrated the therapeutic properties of the oil, such as anti-inflammatory, gastroprotective and healing. Based on this background, the objective of this study was to investigate the antinociceptive and anti-inflammatory oil Pequi (OPCC) in zymosan-induced arthritis in rats. The study was approved by the Ethics Committee on Animal Research of the Federal University of Ceará (nº 83/11). Arthritis was induced by intraarticular injection in right knee of zymosan (1mg/50µL) and evaluated the articular incapacitation (hypernociception), joint swelling, leukocyte migration, cytokine release and expression of inflammatory mediators. The animals were pretreated orally with OPCC (100, 200 e 400mg/kg) or carrier for 7 consecutive days either as a single dose 45 minutes before the induction of arthritis. Dexamethasone, indomethacin or dipyrone were used as positive controls. The articular incapacitation was assessed 4 hours after injection of zymosan. Then the animals were euthanized, proceeding to wash the joint cavity EDTA in PBS for evaluation of leukocyte infiltration, myeloperoxidase activity and cytokine. The tissue synovial fluid was harvested for immunohistochemical analysis of TNF-α and COX-2. We also evaluated edema (transverse diameter of the joint) and increased vascular permeability by the method of Evans blue extravasation. The antinociceptive effect was evaluated further by testing plant mechanical hyperalgesia (von Frey electronic). The results showed a significant decrease (p <0.05) joint of disability in all groups treated with OPCC for 7 days, but with only a single dose, higher doses were effective. Compared to the migration of leukocytes into the synovial fluid all groups treated with the OPCC (single dose and daily doses) showed a significant reduction p <0.05) in the number of leukocytes in the BAL joints, accompanied by a decrease (p <0.05) in myeloperoxidase activity. There was a decrease (p <0.05) cytokine release (TNF-α and IL-1β) in the synovial fluid as well as expression of TNF and COX-2 in synovial tissue. The edema was inhibited (p <0.05) treatment with all doses in OPCC. Moreover, the groups treated with 100 and 400mg/kg of OPCC showed a significant reduction (p <0.05) in vascular permeability. The results also showed that the OPCC significantly reduced (p <0.05) hypernociception and PGE2 induced by carrageenan. The data suggest that the OPCC exhibits anti-inflammatory effect evidenced by arthritis model in rats induced by zymosan, which can be associated with the inhibition of the production of proinflammatory cytokines (TNF-α and IL-1β). Apparently this action may be involved in the inhibition of neutrophil migration. We also suggest that the OPCC hypernociception prevents the development of carragenan-evoked inflammatory mechanical and PGE2 (direct blockade of hypernociception) in rats.